(untitled) (Palíndromo, 2025)
This article seeks to discuss the role of the Jaider Esbell Gallery of Contemporary Indigenous Art, one of the only exhibition spaces in Roraima, in the context of attacks on the Indigenous population and their resistance organizations. This endeavor utilized bibliographical research that began with an interlocution between theories investigating South American capitalism in general and Brazilian capitalism in particular. The emergence of public exhibition spaces—museums—in Europe by the bourgeoisie and their near-nonexistence in the state of Roraima, for an understanding of the broader relationship between exhibition spaces in a peripheral Brazilian state and the attacks suffered by Indigenous peoples in Roraima. Along with this, through the writings of the gallery’s creator, we seek to understand this exhibition space within the historical-social context of affirmation and resistance of Indigenous peoples in northern Brazil. We conclude that the Jaider Esbell Gallery of Contemporary Indigenous Art, more than just an exhibition space, is a space for collective struggle, denunciation, and proclamation of these peoples.